Contratações públicas sustentáveis no estado de São Paulo - Oliveira, Simone Martins (2011)
Sustainable public procurement incorporates environmental and social aspects in the purchasing process and government contracts. The practice of sustainable procurement is spreading through the world and several Brazilian cities and states have specific legislation that deals with environmental aspects. Thus, the objective of this research is to analyze the program implementation and results in hiring and sustainable procurement, with focus on the State Program for Sustainable Procurement in the State of São Paulo. The motif of this choice is explained by the fact that the São Paulo State Government was one of the first Brazilian states to integrate social and environmental criteria into public procurement, with the creation of a work force to promote adoption of environmental sustainability in contracting jobs, services and purchases in 2004, and which has become a reference in sustainable procurement to other states. In order to carry out this research, three evidence sources were used: interviews, documental research and archives. The subject is studied by several international bodies such as UK Sustainable Procurement Task Force, Marrakesh Task Force on Sustainable Public Procurement, ICLEI, and the European Sustainable Development Network. For these organizations in case of Public Procurement, the sustainable public purchase should consider the consequences of environmental, social and economic. The study results show the organization of the State of Sao Paulo in order to implement a program with Sustainable Public Procurement legislation; creation of committees to study this subject, course development in order to capacitate professionals involved on public procurement; the standardization of public notice; through outsourced services contract with the inclusion of social and environmental criteria and registration of materials to specifications of products to these criteria, creation of the Environmental Seal stamped on all the specifications of services and products that have been studied and standardized; creating a website to disseminate information on the subject, and reporting on progress of actions. These reports demonstrated few quantitative data, the information is still in a qualitative stage, i.e., with descriptions of the practices adopted without many concrete results.